Fetal and maternal outcomes and risk factors associated with preterm prelabour rupture of membrane - Thapa, Anita; Medhi, Robin (International Journal of Research in Medical Sciences, 2023)
Background: This study aimed to assess the fetomaternal outcome of preterm prelabour rupture of membranes (PPROM) and identify the risk factors associated with this condition. Methods: The study was conducted in the Obstetrics and Gynecology department of Fakhruddin Ali Ahmed Medical College and Hospital, Barpeta, Assam, and used a hospital-based prospective observational study design. The study duration was 12 months from September 2021 to August 2022, and the sample size was 80. Results: The study found that the majority of respondents were between the ages of 20-25, Hindu, and unemployed. The occurrence of PPROM was most frequent in women between 35-36 weeks of gestation, with 41 patients (51.25%) affected. Approximately 57.50% of the study participants presented to the medical facility within 6 hours of experiencing vaginal discharge. Conclusions: Although PPROM is a common pregnancy complication, its consequences can be avoided by using antibiotics, corticosteroids, and other medications. The majority of the mothers had no risk factors. The study's findings may help healthcare providers to better understand the risk factors associated with PPROM and develop interventions to improve maternal and fetal outcomes.